2020
DOI: 10.51153/mf.v15i1.405
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Capital Adequacy of Nigerian Banks

Abstract: A reliable banking system in developing economies like Nigeria is vital for economic progress as it facilitates the flow of funds to productive investment sectors. The capital adequacy requirement of banks is a crucial feature of the stability of the banks globally. Because of its importance, we have examined the antecedents to capital adequacy. We have used the data set of ten leading banks of Nigeria from 2007 to 2017. Our results indicate that ROA and loan to total assets are significantly associated with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 24 publications
4
11
1
Order By: Relevance
“…An increase in capital adequacy ratio resulted in a decrease in NPL, which affirmed that CAR played a positive role in the reduction of business risks including non-performing loans. The results are in accordance with earlier research conducted by Abiodun et al (2020) and Yulianti et al (2018).…”
Section: Regulatory Capital and Non-performing Loans (Npl)supporting
confidence: 93%
See 2 more Smart Citations
“…An increase in capital adequacy ratio resulted in a decrease in NPL, which affirmed that CAR played a positive role in the reduction of business risks including non-performing loans. The results are in accordance with earlier research conducted by Abiodun et al (2020) and Yulianti et al (2018).…”
Section: Regulatory Capital and Non-performing Loans (Npl)supporting
confidence: 93%
“…In this respect, Yulianti et al (2018) conducted a study on the relationship between capital adequacy ratio effect non-performing loans in public banks of Indonesia for the year 2012 to 2016 and found a positive impact of capital adequacy ratio on non-performing loans. Likewise, Abiodun et al (2020) carried out a study in Nigerian banks of ten leading banks from 2007 to 2017 and found that non-performing loans are negatively related to capital adequacy. Based on the results of Abiodun et al (2020) and Yulianti et al (2018), we suggested the following hypothesis: H3: There is a negative relationship between capital adequacy ratio and non-performing loans.…”
Section: Regulatory Capital and Non-performing Loansmentioning
confidence: 99%
See 1 more Smart Citation
“…These results correspond previous studies by Hadjixenophontos & Christodoulou-Volos (2018), Rianto &Salim (2020), andFatra et al (2020), which concluded that banks' return on assets has no effect on their capital adequacy ratio. These findings contradict those of Cahyono & Anggraeni (2015), Abiodun et al (2020), Hengkeng et al (2018), and Putri & Dana (2018, who concluded that Return on Assets had a positive and substantial effect on Capital Adequacy Ratio. Meanwhile, Dao & Nguyen (2020) concluded that Return on Assets had a considerable negative impact on the Capital Adequacy Ratio.…”
Section: Effect Of Return On Assets On the Capital Adequacymentioning
confidence: 73%
“…The provision of BASEL of CAR has played a major role to deduct the dominance of large banks that ensures the growth of the bank. Abiodun et al (2020) examined that the capital adequacy ratio had a significant strong positive relationship with the profitability of the bank. They also found that capital adequacy ratio has among the main predictors of mid-tier commercial banks' financial performance.…”
Section: Literature Reviewmentioning
confidence: 99%